Analisis Ketidakberaturan Horizontal Struktur Rangka Gedung Oval Dengan Pushover Analysis Pada Rumah Sakit UPT Vertikal Surabaya - Safriana Wahdi, Yudha; Kartini, Wahyu; Dwi Puspitasari, Nia (Kadiri University, 2024)
Building A at the Surabaya UPT Vertical Hospital is an example of using limited land to meet space needs. However, the oval shaped geometry of the building causes the frame structure to be different from usual. This changes in geometry has an impact on the occurences lateral and mass irregularities in the building structure. This study aims to analyze the stability and performance of oval structures by considering the influence of earthquake loads. The capacity level of structure is evaluated using the Performance Based Design method. This method involves conducting a Pushover Analysis by applying a predefined lateral dynamic load to the structure and gradually increasing it until the structure reaches its maximum capacity, ultimately leading to the structural failure. The results of this research obtained a ductility value of 1.21 for the X axis and 1.46 for the Y axis, this value makes the structure classified as partially ductile and not fully ductile. The performance level of the structure on the longitudinal axis (X) is 0.002 and on the transverse axis (Y) is 0.0019, so the structure is classified as SP-1 Immediate Occupancy, which means that the damage caused is not dangerous even if an earthquake occurs. The results of this research can be used as a guide in planning and evaluating oval or other irregular building structures, especially for vital buildings in areas with high earthquake risk.